Some Lessons from Korea's Industrialization Strategy and Experience - Leonardo L. Sta. Romana (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We look at Korea's industrialization strategy and experience from the 1960s to the mid-1990s. Three elements of the Korean industrial development and structural change are discussed: 1) its outward orientation and export push, 2) its climb up the ladder of comparative advantage, and 3) its economic management of the industrialization effort. Finally, we reflect on the lessons from the Korean experience.
Additional information: This paper was written in response to a call for papers by the Global Development Network, a public international organization headquartered in New Delhi, with an office in Washington, DC.
Keywords: F14; L52; N65; O14; 330; South Korea; Industrialization; East Asia; Economic Planning; Economic Growth; Japanese Economic Model; South Korea; Industrialization; East Asia; Development planning; Economic Growth; Japan